2018
DOI: 10.1007/s00192-018-3700-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of postvoid residual volumes after vaginal delivery: a prospective equivalence study to compare an automatic scanning device with transurethral catheterization

Abstract: The BladderScan® (BVI 9400) measures PVRV precisely and reliably after vaginal delivery and should be preferred over catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
1
16
0
2
Order By: Relevance
“…In routine clinical practice, assessment is usually limited to symptomatic postnatal women or women with risk factors for PUR. While some authors have expressed their concerns about the accuracy of 3D Doppler bladder ultrasound scan postnatally, a number of validation studies have shown that automatic scanning devices measure PVR precisely and reliably after vaginal delivery and should be preferred over catheterisation …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In routine clinical practice, assessment is usually limited to symptomatic postnatal women or women with risk factors for PUR. While some authors have expressed their concerns about the accuracy of 3D Doppler bladder ultrasound scan postnatally, a number of validation studies have shown that automatic scanning devices measure PVR precisely and reliably after vaginal delivery and should be preferred over catheterisation …”
Section: Methodsmentioning
confidence: 99%
“…While some authors have expressed their concerns about the accuracy of 3D Doppler bladder ultrasound scan postnatally, 45 a number of validation studies have shown that automatic scanning devices measure PVR precisely and reliably after vaginal delivery and should be preferred over catheterisation. 46,47 There is no evidence for active management of covert PUR with catheterization as this condition resolves within 4 to 7 days. 6 Regarding the treatment of overt PUR, clean intermittent catheterization (CIC) is associated with shorter duration of intervention compared with transurethral indwelling catheterization.…”
Section: Postpartummentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the latest prospective study of Mulder et all, the reliability of measuring PVR with the BladderScan ® (BVI 9400) is promising, according to a sensitivity of 85.4% and sensitivity of 85.6% with a cut-of range for PVR >500 ml directly postpartum [14]. Even though it is a methodically wise strong and large study, it also is the first which used the newer BladderScan ® (BVI 9400).…”
Section: Commentmentioning
confidence: 99%
“…The three-dimensional bladder ultrasonography (BladderScan ® (US, using the BVI 3000 ® , Verathon, WA, USA) is most commonly used method in the Netherlands for determination of PVR in postoperative patients. However, the reliability of the BladderScan ® in the postpartum period are conflicting [1,[9], [10], [11], [12], [13], [14]].…”
Section: Introductionmentioning
confidence: 99%